PENDAMPINGAN MANAJEMEN USAHA PRODUKSI MODIFIED CASSAVA FLOUR (MOCAF) BAGI KWT NGUDI SARI, DESA KEMIRI, KECAMATAN TANJUNGSARI, GUNUNG KIDUL - Astuti, Fatma Hermining; Jatiningrum, Wandhansari Sekar (Universitas Ahmad Dahlan, Yogyakarta, 2019)
KWT Ngudi Sari is one of the farmer groups in Kemiri Village, Gunung Kidul which is actively produce various processed cassava products, such as mocaf flour. The abundant yield of cassava in Kemiri Village and the advantages of mocaf flour, which is good for health become the opportunity for KWT Ngudi Sari to develop their business. However, KWT Ngudi Sari faced several obstacles in their business management that were carried out, such as the lack of detailed calculations for selling prices, unclear division of labor within the organization, SOPs had not been written with good standard flow, and the labels of mocaf flour packaging does not meet the standards. For this reason, a series of community service activity programs in the form of counseling and assistance for KWT Ngudi Sari were designed, specifically to develop mocaf flour processed businesses. These activities include counseling and mentoring related to organizational design, determining the cost of production, selling prices, and BEP, counseling and preparation of informative SOPs, as well as counseling and assistance in making good and standard packaging labels.